Estimation of the Entropy Numbers and Kolmogorov Widths for the Nikol’skii–Besov Classes of Periodic Functions of Many Variables - Romanyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We establish order estimates for the entropy numbers of the Nikol’skii–Besov classes B_p,θ^r of periodic functions of many variables in the space L_q with certain relations between the parameters p and q. By using the obtained lower estimates of the entropy numbers, we establish the exact-order estimates for the Kolmogorov widths of the same classes of functions in the space L_1.